Associate Editor - Savva, Christos S. (My University, 2026)
1. Assign reporting tasks to reporters and correspondents.2. Conduct daily meetings on editorials.3. Lead, guide and direct reporters and assigned feature writers in developing news stories and features.4. Edit, revise and rewrite content copies in accordance to the established procedures and standards.5. Interact and confer with staff writers and authors.6. Determine and decide on editorial stories in consultation with the staff writers.7. Provide technical guidance with regard to graphic design and content.8. Ensure compliance of best practices and standards in journalism.